Fostering Community Resilience and Social Inclusion in the Face of Anti-Homeless NIMBYism - Marcus Sibley; Carrie Sanders; Danielle Thompson; Natasha Martino; Erin Dej; Samantha Henderson (International Journal on Homelessness)
Homelessness has been framed as a growing crisis. People experiencing homelessness often face social exclusion and isolation as a result of policies and practices that promote a “Not in My Backyard” (NIMBY) philosophy. NIMBYism is most recognizable in its efforts to actively oppose affordable housing projects and challenge the efficacies of social servicing in the name of preserving existing neighbourhood dynamics and maintaining property values. These exclusionary discourses and practices have been challenged by a countermovement known as “Yes in my Backyard” (YIMBYism), which advocates for equitable and inclusive housing options and more impactful community programming. To better highlight the tensions between these two movements, this paper provides one of the first comprehensive reviews of multidisciplinary literature on NIMBYism and YIMBYism as they relate to homelessness. We frame the comprehensive review within a community resilience framework — a term used in disaster and emergency management—to shed light on ways communities can foster and promote community resilience in the face of techniques of social and physical exclusion.